Reduced methane seepage from Arctic sediments during cold bottom-water conditions - Ferré, Benedicte; Jansson, Pär; Moser, Manuel; Serov, Pavel; Portnov, Aleksei D; Graves, Carolyn; Panieri, Giuliana; Gründger, Friederike; Berndt, Christian; Lehmann, Moritz F.; Niemann, Helge (Nature Geoscience, 2020)
Large amounts of methane are trapped within gas hydrate in subseabed sediments in the Arctic Ocean, and bottom-water warming may induce the release of methane from the seafloor. Yet the effect of seasonal temperature variations on methane seepage activity remains unknown as surveys in Arctic seas are conducted mainly in summer. Here we compare the activity of cold seeps along the gas hydrate stability limit offshore Svalbard during cold (May 2016) and warm (August 2012) seasons. Hydro-acoustic surveys revealed a substantially decreased seepage activity during cold bottom-water conditions, corresponding to a 43% reduction of total cold seeps and methane release rates compared with warmer conditions. We demonstrate that cold seeps apparently hibernate during cold seasons, when more methane gas becomes trapped in the subseabed sediments. Such a greenhouse gas capacitor increases the potential for methane release during summer months. Seasonal bottom-water temperature variations are common on the Arctic continental shelves. We infer that methane-seep hibernation is a widespread phenomenon that is underappreciated in global methane budgets, leading to overestimates in current calculations.